DYNAMICS OF ISLAMIC THOUGHT IN THE BALKAN REGION: A Critical Study on Husein Đozo’s Modernist and Reformist Thought - Mekic, Sejad (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
This paper examines the dynamics of Islamic thought found in the Balkan region with special emphasis on the modernist and reformist thought of Husein Đozo (1912-1982). Arguably one of the most prominent Bosnian Muslim scholars in the last two hundred years, H. Đozo was born at a time when the external challenges to the Muslim world were many and its internal problems both complex and overwhelming. Đozo therefore made it his primary goal to reinterpret the teachings of Islam to a generation for whom the truths and realities of their religion had fallen into disuse. And indeed, with his numerous works and other scholarly engagements and efforts, Husein Đozo represents a rare and precious example of an indigenous Balkan Muslim scholar who recognised the impact of modernity on religious traditionalism. Even a brief survey of Đozo’s scholarly efforts will tell one that he raised his voice against dogmatism and rigid Islamic thought.